Preliminary Validation Results of a Novel Concept of Operations for RPAS Integration in TMA and at Airports - Schwoch, G.; Duca, G.; Ferraiuolo, V.; Filippone, E.; Lanzi, P.; Teutsch, J.; Petersen, C.C.; Rocchio, R.; Sangermano, V. (IOPScience, 2023)
The paper describes the results of recent research activities carried out to investigate the safe integration of Remotely Piloted Aircraft System (RPAS) into ATC controlled airspace with a focus on Terminal Manoeuvring Areas (TMAs) and airports. The research activities presented in this paper started with the definition of RPAS-specific use cases and the development of a preliminary novel Concept of Operations. This was followed by the definition and the execution of a simulation test plan for the validation of this new operational concept. The validation campaign has been carried out involving aerospace research centres in the Netherlands (Royal NLR), Germany (DLR), and Italy (CIRA), respectively. Different aspects of RPAS integration in the TMA were considered, such as latency of command & control (C2) link and voice communication link, Automatic Take-off and Landing (ATOL) operations, contingency procedures, and handover of control between two different remote pilot stations. The validation exercises were conducted using real-time human-in-the-loop simulation facilities to assess the human performance of both air traffic controllers and remote pilots. The results showed that the proposed novel concept of operations is suitable for the integration of RPAS at TMAs and airports, with 80% of the objectives fully and 20% partially achieved, and acceptable to excellent results regarding acceptance/situational awareness (8.2/9.0 out of 10 points; higher is better) and workload (2.6 out of 10 points; lower is better).